Characterization and genetic dissection of resistance to spotted alfalfa aphid (Therioaphis trifolii) in Medicago truncatula - Kamphuis, L.; Lichtenzveig, Judith; Peng, K.; Guo, S.; Klingler, J.; Siddique, K.; Gao, L.; Singh, K. (Oxford University Press, 2013)
Aphids cause significant yield losses in agricultural crops worldwide. Medicago truncatula, a model legume, cultivated pasture species in Australia and close relative of alfalfa (Medicago sativa), was used to study the defence response against Therioaphis trifolii f. maculate [spotted alfalfa aphid (SAA)]. Aphid performance and plant damage were compared among three accessions. A20 is highly susceptible, A17 has moderate resistance, and Jester is strongly resistant. Subsequent analyses using A17 and A20, reciprocal F1s and an A17×A20 recombinant inbred line (RIL) population revealed that this moderate resistance is phloem mediated and involves antibiosis and tolerance but not antixenosis. Electrical penetration graph analysis also identified a novel waveform termed extended potential drop, which occurred following SAA infestation of M. truncatula. Genetic dissection using the RIL population revealed three quantitative trait loci on chromosomes 3, 6, and 7 involved in distinct modes of aphid defence including antibiosis and tolerance. An antibiosis locus resides on linkage group 3 (LG3) and is derived from A17, whereas a plant tolerance and antibiosis locus resides on LG6 and is derived from A20, which exhibits strong temporary tolerance. The loci identified reside in regions harbouring classical resistance genes, and introgression of these loci in current medic cultivars may help provide durable resistance to SAA, while elucidation of their molecular mechanisms may provide valuable insight into other aphid-plant interactions.